Propaganda Through a Prism of a Photographic Image in the Totalitarian States on the Example of the Third Reich - V. S. Zablotskaya (Дискурс)
Introduction. People have long gone to the invention of the method of fixing objects, phenomena not only with the help of graphic activity, since this method took a lot of time and could not fully convey the appearance of the depicted object. The quality and proximity to reality depended not only on the skill of the artist, but also on the genre in which the painting was performed. And, as a result of a huge number of experiments and invested efforts of a dozen of people, in the XIX century they finally found a different way of fixing everyday life. And photography has become this way.Methodology and sources. The research used data from Internet sources, scientific literature on this subject matter. In the study are used a comparative historical method, a structure-functional analysis, a typological approach.Results and discussion. In this paper, we consider how the same reality was transmitted through the prism of photographic images on the example of the Third Reich. The thesis, which we will try to prove, involving not only the history, but also the data of the survey, is as follows: a photograph can convey the attitude of the state to a person and the place of a person in an ideological society.Conclusion. Thus, this paper deals with the transfer of the desired reality through the prism of photographic images on the example of the Third Reich. The author conducted a survey of respondents. The paper proves the theses of the author based on the carried survey.